Absolute quantification of dengue virus serotype 4 chimera vaccine candidate in Vero cell culture by targeted mass spectrometry. Issue 19 (19th September 2015) - Rougemont, Blandine; Simon, Romain; Carrière, Romain; Biarc, Jordane; Fonbonne, Catherine; Salvador, Arnaud; Huillet, Céline; Berard, Yves; Adam, Olivier; Manin, Catherine; Lemoine, Jérôme
<x xml:space="preserve">Abstract</x> Infection by dengue flavivirus is transmitted by mosquitoes and affects tens to hundreds of millions people around the world each year. Four serotypes have been described, all of which cause similar disease. Currently, there no approved vaccines or specific therapeutics for dengue, although several vaccine prototypes are in different stages of clinical development. Among them, a chimeric vaccine, built from the replication machinery of the yellow fever 17D virus, has shown promising results in phase III trials. Accurate quantitation of expressed viral particles in alive attenuated viral antigen vaccine is essential and determination of infectious titer is usually the method of choice. The current paper describes an alternative or orthogonal strategy, namely, a multiplexed and absolute assay of four proteins of the chimera yellow fever/dengue serotype 4 virus using targeted MS in SRM mode. Over 1 month, variability of the assay using a partially purified Vero cell extract was between 8 and 17%, and accuracy was between 80 and 120%. In addition, the assay was linear between 6.25 and 200 nmol/L and could therefore be used in the near future to quantify dengue virus type 4 during production and purification from Vero cells.